1994
DOI: 10.4141/cjas94-103
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cimaterol on growth, carcass characteristics and meat quality in double-muscled Belgian White-blue bulls

Abstract: 1994. Effect of cimaterol on growth, carcass characteristics and meat quality in double-muscled Belgian White-blue bulls. Can. J. Anim. . Thirty-two double-muscled Belgian White-blue bulls, within a liveweight range of 542 (t 3Z) to 722 (! 3l) kg, daily received 0 or 60 pg cimaterol kg-t liveieight in a corn silage diet for 136 (+ 29) d. Cimaterol slightly improved average daily gain from 1.28 to 1.38 kg (P > 0.05). Cbld carcass weight and dressing were increased by cimaterol from 497.0 to 514.6 kg (P < 0.05… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
0
3
1
Order By: Relevance
“…We expected that the higher water content would also coincide with a higher protein content, based on the close relationship between nitrogen deposition and water retention (Geay and Robelin, 1979). The unaltered protein content in the LT muscle was not in accordance with other experiments (Fiems et al, 1993;Boucque, Fiems, Moermans, Cottyn and Sommer, 1994).…”
Section: Discussioncontrasting
confidence: 47%
“…We expected that the higher water content would also coincide with a higher protein content, based on the close relationship between nitrogen deposition and water retention (Geay and Robelin, 1979). The unaltered protein content in the LT muscle was not in accordance with other experiments (Fiems et al, 1993;Boucque, Fiems, Moermans, Cottyn and Sommer, 1994).…”
Section: Discussioncontrasting
confidence: 47%
“…Similarly, Strydom (2009) found greater drip loss ( > 1.79%) in ZH-fed steaks than control steaks; however, RH and clenbuterol groups had intermediate drip loss. In contrast, other studies have indicated no or little variation in drip loss using cimaterol (Fiems et al, 1990;Boucqué et al, 1994).…”
Section: Moisture Lossmentioning
confidence: 75%
“…Evidence of other βAA repartitioning capacity in cattle is well documented. An increase in carcass protein and moisture with a decrease in carcass fat percentage has been shown with clenbuterol (Ricks et al, 1984), cimaterol (Boucqué et al, 1994;Fiems et al, 1995;Dawson et al, 1997), and ractopamine (Parrott et al, 1990;Schroeder et al, 2003b,c). Additionally, Moloney et al (1990) showed an increase in lean and a decrease in fat due to treatment with the βAA L 644,969 .…”
Section: Discussionmentioning
confidence: 94%
“…As with any repartitioning agent, there is a concern of treatment effects on meat shear force and palatability. Other βAA such as clenbuterol, L-644,969 , and cimaterol have been shown to have negative effects on beef shear force (Miller et al, 1988;Boucqué et al, 1994;Moloney et al, 1994). Even the β 1 -agonist ractopamine hydrochloride has been shown to increase beef LM Warner-Bratzler shear force and decrease sensory tenderness scores when supplemented at approximately 300 mg/animal per day (Schroeder et al, 2003a).…”
Section: Introductionmentioning
confidence: 99%